2018
DOI: 10.12669/pjms.342.12298
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of depression, anxiety and stress among the undergraduate physiotherapy students

Abstract: Objectives:To assess the frequency of Depression, Anxiety and Stress (DAS) among the undergraduate physiotherapy students.Methods:A descriptive cross sectional study was conducted in various Physiotherapy Institutes in Sindh, Pakistan among undergraduate physiotherapy students. The total duration of this study was 4 months from September, 2016 to January, 2017. Data was collected from 267 students with no physical and mental illness; more than half were female students 75.3%. They were selected through Non pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 18 publications
2
72
4
2
Order By: Relevance
“…In relation to the second research question (Did sex in uence the amount of stress and burnout experienced? ), the median age of female participants was 23 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) and for males was 26.5 (21-36) years, with strong evidence for signi cance between groups (p=0.012) [ Table 2]. There was no statistically signi cant difference between groups in relation to their previous degree [ Table 2].…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the second research question (Did sex in uence the amount of stress and burnout experienced? ), the median age of female participants was 23 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) and for males was 26.5 (21-36) years, with strong evidence for signi cance between groups (p=0.012) [ Table 2]. There was no statistically signi cant difference between groups in relation to their previous degree [ Table 2].…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…The ability to cope with stress is an important factor affecting a DPHTY student's success in an academic program 11 . Syed and colleagues 23 reported the frequency of depression, anxiety and stress was 48%, 69% and 53% respectively, amongst undergraduate physiotherapy students in Pakistan 23 . Stress and burnout can furthermore affect students' emotional wellbeing and can result in psychological morbidity 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The median age of female participants was 23 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) and for males was 26.5 (21-36) years, with strong evidence for signi cance between groups (p = 0.012) [ Table 1]. The percentage of those that had previously completed a Bachelor's degree was 87%, with the remaining 13% completing a Masters degree.…”
Section: Resultsmentioning
confidence: 99%
“…Stress and burnout can furthermore affect students emotional wellbeing and can result in psychological morbidity. One study reported that among undergraduate physiotherapy students, the frequency of depression, anxiety and stress was 48%, 69% and 53% respectively 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Globally, among many psychiatric health problems, psychological morbidities are most common and mental health among university students is, now a day's an important and developing public health concern [10]. Stress among university students arise from both academic and non-academic factors, also including socio-economic and cultural, environmental and psychological attributes [11].…”
Section: Discussionmentioning
confidence: 99%